Manufacturing of Electrolyte and Cathode Layers SOFC Using Atmospheric Spraying Method and Its Characterization - S. Sulistyo; S. Ariffin; S. Mahzan (Chemical Engineering Diponegoro University, 2013)
The use of Solid Oxide Fuel Cell (SOFC) has created various interest in many parties, due to its capability to convert gases into electricity. The main requirement of SOFC cell components is to be produced as thin as possible to minimize the losses of electrical resistance, as well as able to support internal and external loads. This paper discusses the procedure of making a thin electrolyte layer, as well as a porous thin layer cathode using atmospheric spraying technique. The procedure of spraying was in room temperature with the process of sintering at temperature of 13500 C held for 3 hours. The SOFC characterization of electrolyte and cathode microstructure was determined by using the SEM, FESEM, XRD and impedance spectroscopy, to measure the impedance of SOFC cells. The results show that the thickness of thin layer electrolyte and porous cathode obtained of about 20 µm and 4 µm, respectively. Also the SOFC cell impedance was measured of 2.3726 x 106 Ω at room temperature. The finding also demonstrated that although the materials (anode, cathode and electrolyte) possess different coefficient thermal expansion, there was no evidence of flaking layers which seen the materials remain intact. Thus, the atmospheric spraying method can offer an alternative method to manufacturing of SOFC thin layer electrolyte and cathode. [Key words: SOFC; spraying method; electrolyte; cathode]